THE PROBLEMS OF E-LEARNING PROJECTS MANAGEMENT IN INSTITUTES OF HIGHER EDUCATION (LAC EXPERIENCE) (Journal of Information Technologies in Education (ITE), 2010)
The problems of e-Learning projects management in Institutes of higher education in particular risks control and after project support are examined in the article. The identified projects’ risks with the use of brain storm methods and mental maps are described. The results of after project support for the e-Learning projects in the conditions of higher educational establishment on the example of the Lviv Academy of Commerce (LАC) are analyzed.
Keywords: after project support; e-Learning projects; risk management